Memorias negras: desenterrado la pedagogía negra (1994-1997) (2020)
Memorias Negras: Desenterrando la Pedagogía Negra is a project born from a personal questioning of the behavior we have with our parents in adulthood and how this could be influenced by our childhood. This project recognizes that socially accepted forms of child pedagogy are not always appropriate and can have negative consequences for the future of children. The project is built around the exploration of topics such as: inappropriate acts, punishments or calls for attention, search for obedience and manifestations in adulthood. This, with the aim of understanding the impact in our adult personality, the way in which we were educated in our childhood. This project begins with a personal inquiry, which leads to the formulation of an initial research question, which is approached from different related disciplinesas psychology, psychoanalysis and sociology to reach a documented answer. The resolution of the initial question leads to the identification of a phenomenon at the individual level that is intended to be validated on a collective level. For this, the Conversaciones Narrativas design methodology is used and appropriated, with the purpose of reconstructing stories through the qualitative analysis of the experiences of each conversational couple and understanding their reality. The reconstruction of these stories makes it possible to identify traits of Black Pedagogy in the reality of each individual, making its roots visible in childhood experiences. The form of representation of the stories is carried out in the form of short stories, bringing together all the narrations in an editorial piece entitled Black Memories, which has an introduction and a final moral with the aim of sensitizing the reader about the importance of making visible and generate reflections on this phenomenon.